2003
DOI: 10.1051/0004-6361:20031047
|View full text |Cite
|
Sign up to set email alerts
|

The blue host galaxy of the red GRB 000418

Abstract: Abstract. We report on multi-band (UBVRIZ J s K s ) observations of the host galaxy of the April 18, 2000 gamma-ray burst. The Spectral Energy Distribution (SED) is analysed by fitting empirical and synthetic spectral templates. We find that: (i) the best SED fit is obtained with a starburst template, (ii) the photometric redshift is consistent with the spectroscopic redshift, (iii) the colours of the host are inconsistent with an old stellar population, and (iv) the global extinction is constrained to be in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 40 publications
5
34
0
Order By: Relevance
“…Pre-Swift studies showed a > ∼ 3σ detection rate at 850 µm of 2/26 hosts, ∼8% (Tanvir et al 2004). Moreover, the blue colors of these brightest hosts at submm wavelengths (e.g., GRB 000418, GRB 010222: Le Floc'h et al 2003;Gorosabel et al 2003) are not typical of galaxy populations selected in submm surveys. Of 15 GRBHs around z ∼ 1, only three were detected at 24 µm with Spitzer (GRB 970828, GRB 980613, GRB 990705: Le Floc'h et al 2006).…”
Section: Dust Stars and Sfrmentioning
confidence: 96%
“…Pre-Swift studies showed a > ∼ 3σ detection rate at 850 µm of 2/26 hosts, ∼8% (Tanvir et al 2004). Moreover, the blue colors of these brightest hosts at submm wavelengths (e.g., GRB 000418, GRB 010222: Le Floc'h et al 2003;Gorosabel et al 2003) are not typical of galaxy populations selected in submm surveys. Of 15 GRBHs around z ∼ 1, only three were detected at 24 µm with Spitzer (GRB 970828, GRB 980613, GRB 990705: Le Floc'h et al 2006).…”
Section: Dust Stars and Sfrmentioning
confidence: 96%
“…Hereafter the derived stellar properties will refer exclusively to the dominant population. Detailed analyses of the SEDs of the host galaxies of GRB 000210, GRB 000418, and GRB 990712 are presented by Gorosabel et al (2003a), Gorosabel et al (2003b), and Christensen et al (2004), respectively. Similar thorough individual SED analyses are beyond the scope of this paper.…”
Section: Spectral Energy Distributionsmentioning
confidence: 99%
“…Alternatively, as shown from the analysis of the GRB 000418 host in Gorosabel et al (2003b), the metallicity is not strongly constrained in the case where the SED is analysed through broad band magnitudes.…”
Section: Ages and Metallicitiesmentioning
confidence: 99%
“…A recent modeling of UV-NIR photometric SED, assuming Calzetti et al (2000) extinction curve, found an average host extinction of AV = 1.3 mag (Perley et al 2013;Schady et al 2014). The R-band image of the host (Figure 1) has been obtained with ALFOSC at the Nordic Optical Telescope approximately one year after the burst (Gorosabel et al 2003b).…”
Section: Grb 000418 Hostmentioning
confidence: 98%
“…The hosts of GRB 000210 (Gorosabel et al 2003a), GRB 000418 (Gorosabel et al 2003b;Hatsukade et al 2011), GRB 000911 (Price et al 2002a;Masetti et al 2005), GRB 080413B, GRB 100316B and GRB 100724A, were selected because, due to their redshift (in the range 0.8 < z < 1.3), they were either lacking the measured values of metallicity, dust extinction and SFR or these quantities were very poorly constrained. The spectral coverage and sensitivity of the X-Shooter allows us to get the whole set of lines (…”
Section: The Samplementioning
confidence: 99%